Exceptional adsorption and separation properties of the molecular sieve ZIF-8 - Böhme, Ulrike; Paula, Carolin; Marthala, Venkata; Caro, Jürgen; Hartmann, Martin (Chemie Ingenieur Technik, 2013)
Low-temperature rectification represents the state-of the-art in olefin/paraffin separation. Adsorption on microporous coordination polymers could be a less energy and cost-intensive alternative. Especially zeolitic imidazolate frameworks, such as ZIF-8, exhibits an interesting adsorption behavior since alkanes are preferentially adsorbed in comparison with the corresponding olefins. The single-component adsorption isotherms and mixed gas breakthrough experiments of C to C hydrocarbons show the potential of ZIF-8 for olefin/paraffin separation. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Adsorption isotherms; Breakthrough curves; Metal organic frameworks; Olefin/paraffin separation